Machine perfusion for liver transplantation: opportunities and challenges for the next generation of transplant surgeons - Mullens, Cody L.; Shanmugarajah, Kumaran; Wakam, Glenn K. (Frontiers in Transplantation, 2026)
Machine perfusion is reshaping liver transplantation by turning preservation from passive storage into an active, physiologic intervention. This review synthesizes randomized and real-world evidence on hypothermic oxygenated and normothermic approaches and translates these data into practical guidance for training programs. Across studies, hypothermic oxygenated perfusion reduces ischemic biliary injury, especially in donation after circulatory death, while normothermic perfusion lowers early biochemical injury, decreases early allograft dysfunction, and increases organ utilization through ex situ viability testing. Contemporary cohorts show that “back-to-base” workflows can lessen early complications without increasing ninety-day costs, and that extended preservation, often paired with donor-care unit models, shifts many cases into planned daytime surgery. These operational gains matter for education: daytime cases enable rested faculty, deliberate practice, and graded autonomy. Perfusion broadens the case mix, and the pump itself introduces teachable competencies in setup, troubleshooting, and data-driven accept or decline decisions. Challenges include potential erosion of donor procurement experience, uneven access, and a still-evolving science of viability. We propose a competency-based curriculum spanning setup and safety, physiology, assessment and decision-making, and systems leadership, and outline research priorities as an area of inquiry for future transplantation surgeon-scientists in their training. Aligning training with this platform will improve care and strengthen the transplant workforce.